SCUBA divers above the waterline: Using participatory mapping of coral reef conditions to inform reef management. (February 2017) - Loerzel, Jarrod L.; Goedeke, Theresa L.; Dillard, Maria K.; Brown, Greg
Abstract: Coral reefs provide important ecological services such as biodiversity, climate regulation, and cultural benefits through recreation and tourism. However, many of the world's reefs are declining, with Caribbean reefs suffering a significant decline in living corals over the past half century. This situation emphasizes the need to assess and monitor reef conditions using a variety of methods. In this study, a new method for assessing reef conditions to inform management using participatory mapping by coral reef "experts" in the U.S. Virgin Islands (USVI) is described. Occupational SCUBA divers were recruited (n=87) to map coral reef conditions, uses, and threats (stressors) using an internet-based mapping website. The data reveal an uneven geographic distribution of reef conditions in the USVI with the most frequently mapped perceived healthy reef characteristics being: large amount of physical reef structure (n=872 markers); endangered or threatened species present (n=721); and large amount of live coral cover (n=615). The greatest perceived threats were: invasive species (n=606); water pollution (n=234); and unsustainable fishing (n=200). Areas of important reef characteristics, perceived threats to reefs, and perceived recovery potential were plotted to identify areas requiring critical management attention. The authors found that perceptions of healthy reef conditions outnumbered perceptions of reef threats for nine of the ten most familiar coral reefs; the most frequent activity type within the coral reefs was tourism diving; and for the most familiar coral reefs, the divers perceived a high recovery potential. Given the novelty of participatory mapping methods to assess coral reefs, the strengths and weaknesses of the method is evaluated. The authors further propose a management typology for categorizing reef areas to inform their future management. In the absence of primary data, or, as a supplement to underwater surveys and remotely-sensed data on reef condition, participatory mapping can provide a cost-effective means for assessing coral reef conditions while identifying place-specific reef locations requiring management attention. Highlights: Evaluates participatory mapping for assessing and monitoring coral reef conditions. Occupational divers mapped reef uses/qualities/threats in US Virgin Islands. Reef conditions and qualities varied by geographic location. Proposes management matrix based on results to inform future reef management. Participatory mapping may provide a cost-effective alternative to biological sampling.